1997
DOI: 10.1038/nm0397-338
|View full text |Cite
|
Sign up to set email alerts
|

The role of viral phenotype and CCR-5 gene defects in HIV-1 transmission and disease progression

Abstract: Cellular entry of human immunodeficiency virus type 1 (HIV-1) requires binding to both CD4 (ref, 1, 2) and to one of the chemokine receptors recently discovered to act as coreceptors. Viruses that infect T-cell lines to form syncytia (syncytium-inducing, SI) are frequently found in late-stage HIV disease and utilize the chemokine receptor CXCR-4; macrophage-tropic viruses are non-syncytium-inducing (NSI), found throughout disease and utilize CCR-5 (ref. 3-11). We postulated that CCR-5 gene defects might reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
251
1
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 439 publications
(266 citation statements)
references
References 21 publications
12
251
1
2
Order By: Relevance
“…1,2 Persons with a homozygous 32 base-pair deletion in the CCR-5 gene, resulting in a truncated protein that remains within the cell, are highly resistant to HIV-1 infection. [9][10][11][12][13][14] This alteration does not affect the health of homozygous carriers, indicating that its functions are dispensable. [9][10][11][12][13][14] Thus, CCR-5 affords an attractive therapeutic target, especially for patients in the early stage of infection.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Persons with a homozygous 32 base-pair deletion in the CCR-5 gene, resulting in a truncated protein that remains within the cell, are highly resistant to HIV-1 infection. [9][10][11][12][13][14] This alteration does not affect the health of homozygous carriers, indicating that its functions are dispensable. [9][10][11][12][13][14] Thus, CCR-5 affords an attractive therapeutic target, especially for patients in the early stage of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Significant studies in the past few years have also demonstrated that innate immunity including genetic polymorphisms in host genes can affect the risk for HIV-1 infection and disease progression (Tab. 1), although the effect of these alleles has been inconsistent [32,[45][46][47][48][49][50][51][52][53][54][55] (reviewed in [56]). Here, we review global and Chinese studies on human genetic polymorphisms and their association with HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…individuals that are CCR5-32 homozygotes (people who inherited the CCR5-32 from both parents) are resistant to HIV-1 infection, indicating that genotype CCR5-32 is highly protective against HIV-1 infection [45][46][47][48][49][50]54]. However, this protection is not absolute because rare individuals homozygous for CCR5-32 are infected with HIV-1 strains that may utilize another co-receptor, such as CXCR4 [64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations